Alpha amylase and angiotensin-converting enzyme-1 inhibitory effects of home-made pomegranate molasses - زم, وسام (Latakia University Journal -Medical Sciences Series, 2024)
Pomegranate fruit and its products are rich sources of bioactive compounds, the most important of which are polyphenols. Pomegranate molasses is traditionally prepared in Syria and is considered to have a high nutritional value, which makes it of great importance. This study aims to evaluate the total polyphenols content and the antioxidant, anti-diabetic and anti-hypertensive properties in a number of home-made pomegranate molasses samples (10 samples). The average total content of polyphenols in the ten samples was 140.76±19.41 mg of gallic acid/g of sample. The samples also showed high antioxidant activity through the DDPH-scavenging activity assay, with IC50 values ​​ranging between 0.05-0.13 mg/ml. As for anti-diabetic activity, the IC50 values ​​for inhibiting the alpha-amylase enzyme for pomegranate molasses samples ranged between 0.83 and 3.67 mg/ml, which are values ​​very close to the activity of the reference drug (acarbose). Finally, the rates of ACE inhibition for pomegranate molasses samples ranged between 32-41%, which indicates good antihypertensive effectiveness. As a result, it is recommended to use pomegranate molasses in the diets of diabetics and hypertensive patients in order to maintain blood sugar levels and blood pressure levels within their normal limits, through a synergistic mechanism and not an alternative to drug treatments.